Hubungan antara tekanan darah dan gula darah dengan kemampuan kognitif siswa pada pembelajaran fisika melalui model pembelajaran search, solve, create, and share (sscs) di SMA 4 Bengkulu Utara - Susmiyarti Susmiyarti; Muhammad Farid; Afrizal Mayub (University of Bengkulu, 2019)
ABSTRACT [The Relationship Between Blood Pressure and Blood Sugar with the Cognitive Ability of Students in Physics Learning Through the Search, Solve, Create and Share (SSCS) Learning Model at SMA 4 Bengkulu Utara]. The purpose of this study is to describe the correlation of blood pressure and blood sugar with student achievement in physics learning through the SSCS learning model at SMAN 4 North Bengkulu. The research method is descriptive-analytic with a cross-sectional study approach. From the results of the blood pressure correlation test and student achievement through the SSCS learning model, it was found that p = 0.828> 0.05, which means that the null hypothesis was accepted, that blood pressure did not have a significant relationship with learning achievement. Furthermore, the value of r = 0.022 which has a relationship with the category is very weak. rom the results of the correlation test of blood sugar and student achievement through the SSCS learning model, it was found that p = 0.932> 0.05 which means that the null hypothesis is accepted, that blood sugar does not have a significant relationship with learning achievement. Furthermore, the r value = 0.134 which has a relationship with a very weak category. So from the results of the analysis above, it can be concluded that there is no relationship between blood pressure and blood sugar with physics learning achievement of students of class X MIPA and XI MIPA at SMAN 4 North Bengkulu. Keywords: Blood Pressure; Blood Sugar; Learning Achievement; Physics Learning; SSCS Model. (Received July 9, 2019; Accepted August 5, 2019; Published October 16, 2019) ABSTRAKTujuan penelitian ini yaitu mendeskripsikan hubungan antara tekanan darah dan gula darah dengan kemampuan kognitif siswa pada pembelajaran fisika melalui model pembelajaran SSCS di SMAN 4 Bengkulu Utara. Metode penelitian ini yaitu deskriptif-analitik dengan melalui metode korelasi. Dari hasil uji korelasi tekanan darah dan prestasi belajar siswa melalui model pembelajaran SSCS yang diajarkan secara tidak langsung kepada siswa selama pengambilan data tekanan darah dan gula darah siswa didapat bahwa p=0,828>0,05 yang artinya hipotesis nol diterima yaitu tekanan darah tidak memiliki hubungan yang signifikan dengan kemampuan kognitif. Selanjutnya, nilai r=0,022 yang memiliki hubungan dengan kategori sangat lemah antara tekanan darah dan kemampuan kognitif siswa. Dari hasil uji korelasi gula darah dan kemampuan kognitif siswa melalui model pembelajaran SSCS didapat bahwa p=0,932>0,05 yang artinya hipotesis nol diterima yaitu gula darah tidak memiliki hubungan yang signifikan dengan kemampuan kognitif. Selanjutnya, nilai r=0,134 yang memiliki hubungan dengan kategori sangat lemah. Sehingga dari hasil analisis di atas, dapat disimpulkan bahwa tidak ada hubungan antara tekanan darah dan gula darah dengan kemampuan kognitif fisika siswa kelas X MIPA dan XI MIPA di SMAN 4 Bengkulu Utara. Kata kunci: Tekanan Darah; Gula Darah; Kemampuan kognitif; Pembelajaran Fisika; Model SSCS